The Indirect Impact of Enterprise Architecture on Successful Project Management in UAE Healthcare Organizations - Hadeel Atallah (2025)
The purpose of this research was to examine the indirect impact of enterprise architecture on successful project management in the UAE healthcare sector under the mediating role of effective decision making. The current research adopted a quantitative methodological framework to rigorously examine the subject matter above and study the phenomenon of the proposed relationships in the case of UAE healthcare entities. A survey was distributed to 500 high level healthcare practitioners and decision makers across the UAE (mainly, Abu Dhabi, Dubai, and Sharjah). The findings of the study revealed that, the variable of effective decision making positively mediated the relationship between enterprise architecture and successful project management in the UAE healthcare industry. The combined path regression value for the independent variable of enterprise architecture, through the mediating variable of effective decision making, to the dependent variable of successful project management, was R = 0.789, at a p value of < .0001. These findings revealed that when the enterprise architecture is synchronized through effective decision making, then implementing any change project and managing it to a successful end would not be a challenge. In agreement with evidence from literature, the findings of the current study further illuminated why it is critical to have synergy across organizational functions through a fully integrated enterprise architecture. The challenge of lack of integration and the bottlenecks it can cause to successful project implementation were implied by virtue of the findings confirming the importance of effective decision making across the enterprise as an enabler of success.